Composite polymer electrolyte incorporating WO3 nanofillers with enhanced performance for dendrite-free solid-state lithium battery. Issue 3 (1st February 2023) - Khan, Kashif; Fu, Bowen; Xin, Hu; Beshiwork, Bayu Admasu; Hanif, Muhammad Bilal; Wu, Jintian; Fang, Zixuan; Yang, Jian; Li, Teng; Chen, Cheng; Motola, Martin; Xu, Ziqiang; et al.
Abstract: All solid-state lithium batteries (ASS-LBs) with polymer-based solid electrolytes are a prospective contender for the next-generation batteries because of their high energy density, flexibility, and safety. Among all-polymer electrolytes, PEO-based solid polymer electrolytes received huge consideration as they can dissolve various Li salts. However, the development of an ideal PEO-based solid polymer electrolyte is hindered by its insufficient tensile strength and lower ionic conductivity due to its semi-crystalline and soft chain structure. In order to lower the crystallization and improve the performance of PEO-based solid polymer electrolyte, tungsten trioxide (WO3 ) nanofillers were introduced into PEO matrix. Herein, a PEO20 /LiTFSI/x-WO3 (PELI-xW) (x = 0%, 2.5%, 5%, 10%) solid composite polymer electrolyte was prepared by the tape casting method. The solid composite polymer electrolyte containing 5 wt% WO3 nanofillers achieved the highest ionic conductivity of 7.4 × 10 -4  S cm -1 at 60 °C. It also confirms a higher Li-ion transference number of 0.42, good electrochemical stability of 4.3V, and higher tensile strength than a PEO/LiTFSI (PELI-0W) fillers-free electrolyte. Meanwhile, the LiFePO4 │PELI-xW│Li ASS-LBs demonstrated high performance and cyclability. Based on these findings, it can be considered a feasible strategy for the construction of efficient and flexible PEO-based solid polymer electrolytes for next-generation solid-state batteries.